Iron Isomaltoside 1000 in the Management of Iron-Deficiency Anemia in Patients with Obstetrics and Gynecology - Vineet Mishra; Smit Bharat Solanki (Advanced Concepts in Medicine and Medical Research Vol. 10, 2023)
Background: Pregnant women are more susceptible to iron deficiency anemia (IDA), which is still a major global health concern. IDA is associated with unfavorable consequences for the mother and the newborn. Therefore, iron status during pregnancy may be assessed by a variety of laboratory assays, the most commonly used being serum ferritin (SF) and hemoglobin (Hb). Treatment for IDA frequently involves intravenous iron. Objectives: To assess iron isomaltoside 1000’s effectiveness in treating IDA in patients with obstetrics and gynecological conditions. Materials and Methods: The study included fifty IDA-positive pregnant women from the start of the second trimester until a few days before birth. Over at least fifteen minutes, each of the ladies got 1000 mg of iron isomaltoside 1000. The following tests were used to determine the efficacy: packed cell volume (PCV), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), polymorphs, lymphocytes, eosinophils, monocytes, red cell distribution width (RDW), serum total iron-binding capacity (TIBC), serum ferritin, serum iron, and reticulocytes count. Severe iron deficiency (ID) is defined as ferritin levels less than 30 \(μ\)g/L, whereas mild-moderate ID is defined as ferritin levels between 100 \(μ\)g/L and greater than 30 \(μ\)g/L. Results: Mean age of women with IDA was 35.14±7.183 which ranged from 22 to 53 years. Significant improvement in mean hemoglobin (8.64±0.85 vs. 12.86±0.97, P <0.001), platelet count (115.11±161.22 vs. 3.13±0.68, P <0.001), polymorphs (70.9±34.36 vs. 50.62±6.39, P = 0.0001), lymphocytes (32.24±9.70 vs. 39.68±7.64, P = 0.0001), PCV (31.40±4.46 vs. 39.72±2.56, P = 0.023), MCV (74.51±8.23 vs. 87.14±3.05, P = 0.021) , MCH (23.71±3.77 vs. 31.62±2.10, P = 0.012), MCHC (27.56±2.81 vs. 34.90±2.30, p=0.001), RDW (18.48±3.02 vs. 13.94±1.62, P = 0.004), TIBS (397.1±74.53 vs. 273.86±31.55, P = 0.024), serum ferritin (32.19±78.18 vs. 85.96±21.74, P <0.001), serum iron (46.40±14.89 vs. 108.32±21.38, P <0.001) and reticulocytes (1.84±0.79 vs. 1.07±0.29, P <0.001) after 27th day treatment with Iron isomaltoside 1000 compared to baseline. Iron Isomaltoside 1000 was also able to improve severe ferritin level to mild-moderate ferritin level in a span of 27 days. Conclusion: Iron isomaltoside 1000 is a useful medication for gynecological and obstetric patients. On standard IDA options, a notable improvement was noted.